Généricité Dans Lullaby De J. M. G. Le Clézio. Une Analyse De La « Complexité Des Faits De Discours » - Tossou, Okri Pascal (European Scientific Journal, ESJ, 2017)
J. M. G. Le Clézio represents one of the most eloquent contemporary French writers. This celebrity stems not only from a wide range of biography-based writings but mostly from the contents and aesthetics of his preferences. To me, Lullaby links up these two main facets which cristalize the singular character of Clézio productions. Firstly edited in 1978 by Gallimard in a book of short stories named Mondo et autres histoires, the text reveals itself as a youth novel by the same editor in 1980. Yet, this research apprehends it as a Bildungsroman, from its inner discourse, sharpened within the angle of initiatory convictions. To achieve such a goal, research tools include poetic narrative, sociocritics and discourse analysis.